2008
DOI: 10.1063/1.2936886
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent transport of beam ions

Abstract: The radial redistribution of energetic ions by background turbulence is investigated by means of linear and nonlinear gyrokinetic simulations with the GENE code [T. Dannert and F. Jenko, Phys. Plasmas 12, 072309 (2005)]. The fast particles are described by an asymmetric and anisotropic Maxwellian distribution function, and they are treated as passive tracers. It is found that there can be a significant fast ion diffusivity for particle energies up to about 10 times the thermal energy, with details depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 33 publications
5
35
0
Order By: Relevance
“…Our findings have been shown to be in qualitative agreement with those presented in Refs. [29,31,41], and quantitative discrepancies are due to the difference in the parameters chosen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings have been shown to be in qualitative agreement with those presented in Refs. [29,31,41], and quantitative discrepancies are due to the difference in the parameters chosen.…”
Section: Discussionmentioning
confidence: 99%
“…We note that these pitch angles are characteristic of tangentially injected NBI distributions and ICRH distributions, respectively. For passing ions, a D v ≃ E −1 decay is expected [29][30][31]. For deeply trapped particles, i.e.…”
Section: Velocity Space Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a series of experimental [5,6], theoretical [7] and numerical investigations [8][9][10] demonstrated that this conclusion might not hold for energetic ions created by neutral beam injection: in general, transport can be significant for particles characterized by 'intermediate' energies (E/T e 10) and small Larmor radii.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of modes affect ions in only part of velocity space, for example sawteeth [35][36][37][38], Alfvén eigenmodes [6,[39][40][41][42][43] and neoclassical tearing modes [4,5]. Turbulent transport of fast ions also depends on the ion energy [44][45][46][47]. Additionally, velocityspace tomography could be used to monitor phase-space engineering of fast-ion velocity distribution functions which has enabled control of sawteeth and neoclassical tearing modes [48].…”
Section: Introductionmentioning
confidence: 99%